Juniperus Polycarpos C. Koch forests and its Conservation Status in Cold Deserts of Himachal Pradesh, North West Himalayas - Jishtu, Vaneet; Rawat, R. S. (Indian Forester, 2014)
The article outlines the results of a study carried out for assessing the distribution and ecological status of Juniperus polycarpos C. Koch in cold deserts of Himachal Pradesh, comprising the districts of Lahaul and Spiti and Pooh Subdivision of Kinnaur district. A valley-wise inventory of the cold deserts under the species had been prepared and compared with the available records. Regeneration status and vegetative associates of the species in various valleys of the cold deserts have also been recorded. The results of study show that the species is under great threat due to the ever-increasing biotic pressure and poor natural regeneration. The article also suggested some measures to be initiated for its conservation.